Abortion information-seeking experiences among women who obtained abortions in Kinshasa, DRC: Results from a qualitative study. - Denise Ngondo; Celia Karp; Dynah Kayembe; Kisulu Samyonga Basile; Caroline Moreau; Pierre Akilimali; Suzanne O Bell (Public Library of Science (PLoS), 2024)
Little is known about the process of seeking information related to abortion care options among women in the Democratic Republic of Congo (DRC). Understanding how women obtain information can help identify opportunities for intervention to increase awareness and use of safe pregnancy termination options. Using qualitative data collected from women in Kinshasa, DRC who reported having an abortion in the last 10 years, this study aims to determine how women navigate obtaining information about their options for abortion and the role of their social network in their information-seeking processes. Data for this analysis come from a mixed-method study of abortion in Kinshasa conducted from December 2021 to April 2022. Fifty-two qualitative interviews followed a structured interview guide, including open-ended questions and probes, developed by a multidisciplinary team of researchers in Kinshasa and the United States. Inductive thematic analysis was conducted using Atlas.ti, and a thematic analysis matrix was used to describe the major themes and subthemes. Thematic analysis revealed two main themes with nested subthemes. The first and most salient theme highlighted the highly selective and narrow information search process women engaged in, involving no others or very few individuals (e.g., partners, women in one's community, or providers) that the pregnant woman chose strategically. The second theme revealed the heterogeneous and often stigmatizing nature of these interactions, including attempts at deterrence from many sources and information of varying completeness and accuracy. While the recent liberalization of the abortion law in the DRC is essential to improve access to safe abortion, public health gains will not materialize unless they are accompanied by community-level actions to raise awareness about the legality and availability of safe abortions services, including medication abortion pills for safe self-managed abortion.